Study on the Meshing Stiffness of Spur Gear Considering Contact Characteristic of Tooth Surface - Chen Ruibo; Zhang Jianjie; Zhou Jianxing; Sun Wenlei (Jixie chuandong)
The periodic change of gear pair meshing stiffness is the main internal motivation of gear system vibration,taking the external meshing model of the straight tooth cylindrical gear pair as study object,considering the influence of tooth contact characteristic on the gear stiffness,the contact analysis of finite element model of the gear pair is established,the gear meshing stiffness is calculated,the change situation of gear meshing stiffness is discussed with gear in the case of the axial load and under different load cases. In view of the stress distribution of contact area,the changing reason of the meshing stiffness is researched. It is found that gear meshing stiffness decreased with the increase of axial load. When the meshing gear is subjected to variant loads,the stiffness increased in a linear pattern with the increase of load,and it tended to remain stable after reaching a certain degree.